Human CD34(+) cells express CXCR4 and its ligand stromal cell-derived factor-1. Implications for infection by T-cell tropic human immunodeficiency virus - Aiuti, A; Turchetto, L; Cota, M; Cipponi, A; Brambilla, A; Arcelloni, C; Paroni, R; Vicenzi, E; Bordignon, C; Poli, G (Blood, 1999)
Human CD34(+) hematopoietic progenitor cells obtained from bone marrow (BM), umbilical cord blood (UCB), and mobilized peripheral blood (MPB) were purified and investigated for the expression of the chemokine receptor CXCR4 and its ligand, stromal cell-derived factor-1 (SDF-1). CXCR4 was found present on the cell surface of all CD34(+) cells, although it was expressed at lower density on MPB with respect to BM CD34(+) cells. Freshly isolated and in vitro-cultured CD34(+) cells also coexpressed SDF-1 mRNA, as determined by reverse transcriptase-polymerase chain reaction (RT-PCR). Of interest, CD34(+)/CD38(+) committed progenitor cells, unlike primitive CD34(+)/CD38(-) cells, expressed SDF-1 mRNA. Supernatants from in vitro-cultured CD34(+) cells contained substantial (3 to 8 ng/mL) amounts of SDF-1 by enzyme-linked immunosorbent assay and induced migration of CD34(+) cells. Because CD34(+) cells express low levels of CD4, the primary receptor of the human immunodeficiency virus (HIV), and CXCR4 is a coreceptor for T-cell tropic (X4) HIV strains, we investigated the susceptibility of CD34(+) cells to infection by this subset of viruses. Lack of productive infection was almost invariably observed as determined by a conventional RT activity in culture supernatants and by real-time PCR for HIV DNA in CD34(+) cells exposed to both laboratory adapted (LAI) and primary (BON) X4 T-cell tropic HIV-1 strain. Soluble gp120 Env (sgp120) from X4 HIV-1 efficiently blocked binding of the anti-CD4 Leu3a monoclonal antibody (MoAb) to either human CD4(+) T cells or CD34(+) cells. In contrast, sgp120 interfered with an anti-CXCR4 MoAb binding to human T lymphocytes, but not to CD34(+) cells. However, CXCR4 on CD34(+) cells was downregulated by SDF-1. These results suggest that CXCR4 and its ligand SDF-1 expressed in CD34(+) progenitors may play an important role in regulating the local and systemic trafficking of these cells. Moreover, these findings suggest multiple and potentially synergistic mechanisms at the basis of the resistance of CD34(+) cells to X4 HIV infection, including their ability to produce SDF-1, and the lack of CXCR4 internalization following gp120 binding to CD4.